Pengaruh E-Service Quality, Trust dan Customer Perceived Value terhadap Customer Satisfaction pada Transportasi Online Grab di Kota Metro - Dino, Dino; Suryadi, Suryadi (Jurnal Manajemen DIVERSIFIKASI, 2021)
The purpose of research to determine the influence of e-service quality, trust and customer perceived value on customer satisfaction with the Grab transportation model in Kota Metro. The type of research is quantitative with the object of research is e-service quality, trust, customer perceived value, customer satisfaction. The population of this research is all transport users online Grab in Metro City with a total sample of 97 respondents. The technique of collecting data using questionnaires and literature study. Analyzer uses multiple linear regression analysis.The results showed that partially there is a positive and significant influence of e-service quality on customer satisfaction on Grab online transportation in MetroCity, there is a positive and significant influence of trust on customer satisfaction on Grab online transportation in MetroCity, and there is a positive and significant influence of trust on customer satisfaction on Grab online transportation in MetroCity. Simultaneously there is a positive and significant influence of e-service quality, trust and customer perceived value simultaneously on customer satisfaction on Grab online transportation in Metro City.